On quantum fields at high temperature - Bischer, Ingolf; Grandou, Thierry; Hofmann, Ralf (Universe, 2019)
Revisiting the fast fermion damping rate calculation in a thermalized momentum scale eT (QED) and/or momentum scale gT (QCD) plasma at 4-loop order, focus is put on a peculiar perturbative structure which has no equivalent at zero-temperature. Not surprisingly, and in agreement with previous C ★ -algebraic analyses, this structure renders the use of thermal perturbation theory quite questionable.
Gesehen am 22.05.2019